2016
DOI: 10.3389/fphys.2016.00166
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase-Derived ROS Induced by Chronic Intermittent Hypoxia Mediates Hypersensitivity of Lung Vagal C Fibers in Rats

Abstract: Obstructive sleep apnea (OSA), manifested by exposure to chronic intermittent hypoxia (CIH) and excess production of reactive oxygen species (ROS) in the airways, is associated with hyperreactive airway diseases. ROS, particularly when created by NADPH oxidase, are known to sensitize lung vagal C fibers (LVCFs), which may contribute to airway hypersensitivity pathogenesis. We investigated whether CIH augments the reflex and afferent responses of LVCFs to chemical stimulants and the roles of ROS and NADPH oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Previously, we demonstrated that transient receptor potential vanilloid type 1 (TRPV1) receptors in CB chemosensory afferents are largely responsible for the anandamide and exquisite heat sensitivity of the CB (Roy et al 2012). Because TRPV1 plays an important role in neuronal plasticity in the hippocampus and several sensory systems, and because, in some of these systems, ATP activation of P2X receptor leads to TRPV1 phosphorylation, we hypothesized that TRPV1 receptors contribute to CB sensory LTF (Bhave et al 2003;Marsch et al 2007;Li et al 2008;Hasegawa et al 2009;Shen et al 2012;Lin et al 2013;Saloman et al 2013;Ruan et al 2014;Yang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that transient receptor potential vanilloid type 1 (TRPV1) receptors in CB chemosensory afferents are largely responsible for the anandamide and exquisite heat sensitivity of the CB (Roy et al 2012). Because TRPV1 plays an important role in neuronal plasticity in the hippocampus and several sensory systems, and because, in some of these systems, ATP activation of P2X receptor leads to TRPV1 phosphorylation, we hypothesized that TRPV1 receptors contribute to CB sensory LTF (Bhave et al 2003;Marsch et al 2007;Li et al 2008;Hasegawa et al 2009;Shen et al 2012;Lin et al 2013;Saloman et al 2013;Ruan et al 2014;Yang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, excess ROS plays an important role in the IH-induced sensitization of LVCFs. Similar contributions are also found in the development of LVCF hypersensitivity induced by acute IH (Shen et al, 2012 ) or 14-day chronic IH (Yang et al, 2016 ), as well as the development of several other cardiorespiratory responses induced by IH (Nisbet et al, 2009 ; Edge et al, 2012 ; Schulz et al, 2014 ). IH produces cyclic periods of hypoxia/re-oxygenation, which seems to promote ROS production in the airways (Prabhakar, 2001 ).…”
Section: Discussionmentioning
confidence: 52%
“…The method of general preparations has been described in detail previously (Yang et al, 2016 ). Briefly, at termination of 24 h IH exposure, rats were anesthetized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ROS-based oxygen sensing model, NOX-derived ROS is known to sensitize the lung vagal fibers and is considered to be a major signaling molecule in the chronic hypoxia model. 22 LDS leads to a significant increase in NOX4 levels and redox imbalance. These results indicate that LDS exposure can cause imbalances in the sympathetic and parasympathetic nervous systems.…”
Section: Discussionmentioning
confidence: 99%